Rapid and Extensive Expansion in the United States of a New Multidrug-resistant Escherichia coli Clonal Group, Sequence Type 1193. (29th June 2018) - Tchesnokova, Veronika L; Rechkina, Elena; Larson, Lydia; Ferrier, Kendra; Weaver, Jamie Lee; Schroeder, David W; She, Rosemary; Butler-Wu, Susan M; Aguero-Rosenfeld, Maria E; Zerr, Danielle; Fang, Ferric C; Ralston, James; et al.
Abstract: We describe the rapid and ongoing emergence across multiple US cities of a new multidrug-resistant Escherichia coli clone—sequence type (ST) 1193—resistant to fluoroquinolones (100%), trimethoprim-sulfamethoxazole (55%), and tetracycline (53%). ST1193 is associated with younger adults (age <40 years) and currently comprises a quarter of fluoroquinolone-resistant clinical E. coli urine isolates.